"Żeby mama sobie poszła i już nigdy nie wróciła". Wizerunek rodziny i rodzicielstwa w prasie (na materiale "Wysokich Obcasów") = "Wishing mom would go away and never come back". An image of a family and parenting in the press (based on materials from "The High Heels" ["Wysokie Obcasy"]) - Idzikowska, Magdalena (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article focuses on presenting the unstereotypical parenting roles in the press. These roles differentiate from the images of mother and father established in the language. The image emerging from the linguistic analysis of the texts published in "The High Heels records the family and parenting from the perspective of an adult child or mother (father), less often an expert. The analysed material consists the following written forms - various genres of journalistic texts about the family (letters to the editorial office, articles, conversations, reportages, feuilletons) published in the mentioned magazine.
Keywords: rodzina; media; wizerunek; "Wysokie Obcasy"; family; "The High Heels"